2019
DOI: 10.1055/a-0942-9336
|View full text |Cite|
|
Sign up to set email alerts
|

Cholangioscopy-guided lithotripsy for difficult bile duct stone clearance in a single session of ERCP: results from a large multinational registry demonstrate high success rates

Abstract: Background Peroral cholangioscopy (POCS) can be useful for difficult bile duct stone clearance. Large prospective multinational data on POCS-guided lithotripsy for clearing difficult bile duct stones in a single session of endoscopic retrograde cholangiopancreatography (ERCP) are missing. Methods Patients with difficult bile duct stones (defined as one or more of: largest stone diameter ≥ 15 mm, failed prior attempt at stone clearance, impacted, multiple, hepatic duct location, or located above a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 21 publications
2
38
0
1
Order By: Relevance
“…In four patients, stones were found during their procedure for indeterminate biliary stricture. Data for these four patients were included in both the current study and a previous SpyGlass AMEA registry study of cholangioscopy-guided lithotripsy for difficult bile duct stone clearance [7].…”
Section: Study Design Study Conduct and Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…In four patients, stones were found during their procedure for indeterminate biliary stricture. Data for these four patients were included in both the current study and a previous SpyGlass AMEA registry study of cholangioscopy-guided lithotripsy for difficult bile duct stone clearance [7].…”
Section: Study Design Study Conduct and Patient Populationmentioning
confidence: 99%
“…Since then a prospective, multicenter study was completed in the Asia, Middle East, and Africa (AMEA) regions and included 522 patients who underwent POCS for various indications, including biliary stone disease, as well as indeterminate biliary strictures. The outcomes of a subcohort of this study with difficult biliary stone disease were recently published [7].…”
Section: Introductionmentioning
confidence: 99%
“…27 Data from a large multinational registry demonstrated that a larger size of the largest stone and a higher number of stones had a negative impact on the rate of complete stone clearance in a single session. 28 Cholangioscopy-guided lithotripsy is superior to other methods, including ML or EPLBD, because it can be used as a rescue method after the failure of ML or EPLBD, and is a good alternative to common bile duct (CBD) exploration. Buxbaum et al reported that SOC-guided LL provided a higher stone clearance rate in > 10-mm stones than the conventional methods, including ML and balloon sphincteroplasty (93% vs. 67%, p= 0.009), in a randomized study.…”
Section: Cholangioscopy-guided Lithotripsymentioning
confidence: 99%
“…Overall, the group found that cholangioscopy allowed for direct visualization of stones in 100% of patients, and that stone clearance was successful in a single SOC procedure for 80% of cases. The stones were cleared using either electrohydraulic or laser lithotripsy, with no significant difference in outcomes between the two (74% vs. 82%) The use of SpyGlass also had a significant impact on patient management, leading to a change in diagnosis or therapy in 91% of patients, including 83 patients who no longer needed surgical stone removal [14].…”
Section: Biliary Stonesmentioning
confidence: 99%
“…Direct visual inspection of bile duct strictures may help the determination of benign versus malignant stricture and may also allow for targeted and accurate tissue biopsy ( Figure 2). difference in outcomes between the two (74% vs. 82%) The use of SpyGlass also had a significant impact on patient management, leading to a change in diagnosis or therapy in 91% of patients, including 83 patients who no longer needed surgical stone removal [14].…”
Section: Indeterminate Biliary Stricturesmentioning
confidence: 99%